Gig economy- a rising trend among the millennials and Z generation - Sabli, Nurshamimi (Universiti Teknologi MARA, Terengganu, 2022)
employment in Malaysia and almost all countries worldwide has shifted from the traditional full-time employment to the part-time and flexible employment. This recent employment trend is closely related to the gig economy. The Department of Statistics Malaysia (DOSM) in their newsletter has discussed several definitions and features of those working in this gig economy (i.e., the gig workers) (DOSM, 2020). For instance, according to the International Labour Organization (ILO), gig workers are considered as independent labour who often work in short periods of time or are task-based, with higher presence in online or digital platforms. Using digital platforms, the gig economy connects freelancers or gig workers with customers to provide short-term services, such as Grab app for ride-hailing service, FoodPanda application (app) for food delivery service and Airbnb app for holiday rental service.